Journeys into madness : mapping mental illness in the Austro-Hungarian empire - Blackshaw, Gemma; Wieber, Sabine (Austrian and Habsburg studies ;, 2012)
At the turn of the century, Sigmund Freud's investigation of the mind represented a particular journey into mental illness, but it was not the only exploration of this 'territory' in the Austro-Hungarian Empire. Sanatoriums were the new tourism destinations, psychiatrists were collecting art works produced by patients and writers were developing innovative literary techniques to convey a character's interior life. This collection of essays uses the framework of journeys in order to highlight the diverse artistic, cultural and medical responses to a peculiarly Viennese anxiety about the madness.